Pembinaan Usaha Kreatif dan Inovatif Berbasis Sumber Daya Alam Bagi Masyarakat Desa Buantan Besar Siak - Nurhayati Zein; Afrida; Eniwati Khaidir; Yusrida (Anotero Lembaga Scientific Pekanbaru, 2021)
The coastal village area has various potential resources whose utilization has not been optimal. One of the important potentials to be considered is human resources, with the creative abilities they have, humans are able to create limited and low-value resources into resources of high economic value. Buantan Besar Siak Village is a village located in the coastal area of ​​Siak Regency. This area has a wealth of potential natural resources, including oil palm, rubber and fishermen. This counseling aims to answer the wishes of the community, develop the knowledge and skills possessed by lecturers, provide solutions to community problems, and make natural resources a useful source of income. The results of the service carried out are enthusiastic mothers and young women and feel helped to get useful knowledge. Some recommendations that the author can give are: first, the skills obtained are practiced in daily life; second, the existence of a sustainable service program from related parties; third, the convenience provided by related parties in processes related to service.